Relationship between Competence, Motivation, and Leadership with Performance of Nutrition Workers at Public Health Centers - Meiny O. Manumpil; Nova H. Kapantow; Martha M. Kaseke (Universitas Sam Ratulangi, 2022)
Abstract: Achieving good performance needs to be supported by qualified human resources. Factors that affect performance include competence, motivation, and leadership. This study aimed to determine the relationship between competence, motivation, and leadership with the performance of health workers at public health center. This was a quantitative study. The population consisted of all nutrition workers at public health centers in Manado totaling 48 people; all of them were samples of this study. Data were analyzed by using the Pearson product moment test and the multiple linear regression test. The results showed that the mean of competence variable was 19.69; of motivation variable was 103.2; of leadership variable was 44.19; and of performance variable was 103.02. The Pearson product moment test resulted in p=0.020 for the correlation between competence and performance; p=0.012, for the correlation between motivation and performance; and p=0.200, for the correlation between leadership and performance. The multiple linear regression test showed that motivation had the strongest relationship with performance (p=0,018). In conclusion, there are significant relationships between competence and motivation with performance. Motivation has the strongest relationshipwith performance.Keywords: competence; motivation; leadership; performanceAbstrak: Pencapaian kinerja yang baik perlu didukung oleh sumber daya manusia yang berkualitas. Faktor yang memengaruhi kinerja di antaranya faktor kepemimpinan, faktor pribadi meliputi motivasi, disiplin, keterampilan, faktor sistem, dan faktor situasional atau lingkungan kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara kompetensi, motivasi, dan kepemimpinan dengan kinerja petugas gizi di puskesmas. Jenis penelitian ialah kuantitatif.Populasi ialah seluruh petugas gizi di puskesmas Kota Manado.berjumlah 48 orang dengan populasi total sebagai sampel. Analisis statistik yang digunakan ialah uji Pearson product moment dan uji regresi linier berganda. Hasil penelitian mendapatkan rerata kompetensi 19,69, rerata motivasi 103,2, rerata kepemimpinan 44,19, dan rerata kinerja 103,02. Hasil uji Pearson productmoment menunjukkan nilai p=0,020 untuk korelasi antara kompetensi dengan kinerja; p=0,012 untuk korelasi antara motivasi dengan kinerja; dan p=0,200 untuk korelasi antara kepemimpinan dengan kinerja. Hasil uji regresi linier berganda menunjukkan bahwa variabel motivasi yang paling erat hubungannya dengan kinerja. Simpulan penelitian ini ialah terdapat hubungan bermakna antara kompetensi dan motivasi dengan kinerja petugas gizi di puskesmas. Mottivasi memiliki hubungan yang paling erat dengan kinerja.Kata kunci: kompetensi; motivasi; kepemimpinan; kinerja